Analisa Potensi Booklet Inventarisasi Alat Peraga Halal Culinary art Pada Jajanan Tradisional Sebagai Bahan Ajar Materi Sistem Organ IPA SMP - Raida, Sulasfiana Alfi; Immadudin, Muhammad (Penerbit Widina, Widina Media Utama, 2025)
Science learning at the junior high school level often challenges conveying abstract concepts, especially in the material on the human organ system. One innovation that can improve student understanding is the booklet Inventory of Halal Culinary art Teaching Aids in Traditional Snacks, which integrates traditional food-based teaching aids in learning. This study aims to analyze the potential of the booklet as a teaching material based on teacher and student responses. The method used is quantitative descriptive research involving 23 MGMP Science teachers and 42 junior high school students in Kudus Regency as respondents. Data were collected through a questionnaire covering aspects of appearance, readability, usefulness, and effectiveness in learning the organ system. The results showed that the booklet received a very good response from teachers and students, with an average score of 81%–85% on all aspects measured. Teachers considered the booklet as an interesting and relevant teaching material, while students found it easier to understand the concept of the organ system through visual representations based on traditional snacks. In addition, the integration of cultural and Islamic values in the booklet provides additional benefits in character education. In conclusion, this booklet has high potential as an innovative teaching material that can improve students' understanding of the science organ system and strengthen appreciation of local culture and the concept of halal food.ABSTRAKPembelajaran IPA di tingkat SMP sering menghadapi tantangan dalam menyampaikan konsep abstrak, terutama pada materi sistem organ manusia. Salah satu inovasi yang dapat digunakan untuk meningkatkan pemahaman siswa adalah booklet Inventarisasi Alat Peraga Halal Culinary art pada Jajanan Tradisional, yang mengintegrasikan alat peraga berbasis makanan tradisional dalam pembelajaran. Penelitian ini bertujuan untuk menganalisis potensi booklet sebagai bahan ajar berdasarkan respons guru dan siswa. Metode yang digunakan adalah penelitian deskriptif kuantitatif dengan melibatkan 23 guru MGMP IPA dan 42 siswa SMP di Kabupaten Kudus sebagai responden. Data dikumpulkan melalui angket yang mencakup aspek tampilan, kebermanfaatan, materi, dan pemahaman terhadap materi sistem organ. Hasil penelitian menunjukkan bahwa booklet mendapatkan respons sangat baik dari guru dan siswa, dengan skor rata-rata 81%–85% pada seluruh aspek yang diukur. Guru menilai booklet sebagai bahan ajar yang menarik dan relevan, sementara siswa merasa lebih mudah memahami konsep sistem organ melalui representasi visual berbasis jajanan tradisional. Selain itu, integrasi nilai budaya dan keislaman dalam booklet memberikan manfaat tambahan dalam pendidikan karakter. Kesimpulannya, booklet ini memiliki potensi tinggi sebagai bahan ajar inovatif yang dapat meningkatkan pemahaman siswa terhadap sistem organ IPA serta memperkuat apresiasi terhadap budaya lokal dan konsep makanan halal.